Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Towards Situational Process Management for Professional Education Programmes - Wolters, Dennis; Engels, Gregor (Product-Focused Software Process Improvement)

ARCH-COMP22 Category Report: Stochastic Models - Abate, Alessandro; Blom, Henk; Delicaris, Joanna; Haesaert, Sofie; Hartmanns, Arnd; van Huijgevoort, Birgit; Lavaei, Abolfazl; Ma, Hao; Niehage, Mathis; Remke, Anne; Schön, Oliver; Schupp, Stefan; et al. (EPiC Series in Computing)
This report presents the results of a friendly competition for formal verification and policy synthesis of stochastic models. It also introduces new benchmarks and their properties within this category and recommends next steps for this category towards next year’s edition of the competition. In comparison with tools on non-probabilistic models, the tools for stochastic models are at the early stages of development that do not allow full competition on a standard set of benchmarks. We report on an initiative to collect a set of minimal benchmarks that all such tools can run, thus facilitating the comparison between efficiency of the implemented techniques. The friendly competition took place as part of the workshop Applied Verification for Continuous and Hybrid Systems (ARCH) in Summer 2022.

Model Predictive Torque Control for Permanent Magnet Synchronous Motors Using a Stator-Fixed Harmonic Flux Reference Generator in the Entire Modulation Range - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Multi-Objective Physics-Guided Recurrent Neural Networks for Identifying Non-Autonomous Dynamical Systems - Schön, Oliver; Götte, Ricarda-Samantha; Timmermann, Julia (arXiv:2204.12972)
While trade-offs between modeling effort and model accuracy remain a major concern with system identification, resorting to data-driven methods often leads to a complete disregard for physical plausibility. To address this issue, we propose a physics-guided hybrid approach for modeling non-autonomous systems under control. Starting from a traditional physics-based model, this is extended by a recurrent neural network and trained using a sophisticated multi-objective strategy yielding physically plausible models. While purely data-driven methods fail to produce satisfying results, experiments conducted on real data reveal substantial accuracy improvements by our approach compared to a physics-based model.

Correct-by-Design Control of Parametric Stochastic Systems - Schön, Oliver; Huijgevoort, Birgit van; Haesaert, Sofie; Soudjani, Sadegh (arXiv:2210.08269)
This paper addresses the problem of computing controllers that are correct by design for safety-critical systems and can provably satisfy (complex) functional requirements. We develop new methods for models of systems subject to both stochastic and parametric uncertainties. We provide for the first time novel simulation relations for enabling correct-by-design control refinement, that are founded on coupling uncertainties of stochastic systems via sub-probability measures. Such new relations are essential for constructing abstract models that are related to not only one model but to a set of parameterized models. We provide theoretical results for establishing this new class of relations and the associated closeness guarantees for both linear and nonlinear parametric systems with additive Gaussian uncertainty. The results are demonstrated on a linear model and the nonlinear model of the Van der Pol Oscillator.

Scikit-Weak: A Python Library for Weakly Supervised Machine Learning - Campagner, Andrea; Lienen, Julian; Hüllermeier, Eyke; Ciucci, Davide (Lecture Notes in Computer Science)

Review on: Daniel Benedikt Stienen: Verkauftes Vaterland - Schönhärl, Korinna (Sehepunkte)

Review on: Sven Steinmo: Willing to Pay? A Reasonable Choice Approach - Schönhärl, Korinna (HSozKult)

‚Understand what’s happening within‘. Selbstkontrolle mit Personenwaage, Wearable und habit tracker - Schloots, Franziska Margarete (ffk Journal)
Mit steigenden Optimierungsanforderungen an das Individuum wächst auch das indivi- duelle Bedürfnis nach Kontrolle. Dieses kann u. a. durch self tracking-Technologien erfüllt werden. Anhand von drei Fallbeispielen – der Personenwaage, dem Wearable und dem habit tracker – zeigt dieser Aufsatz, wie sich medienbasierte Selbsttechnologien im historischen Verlauf intensiviert und stärker in den Alltag integriert haben. Ein besonderer Fokus liegt dabei auf der Ambivalenz dieser Medien: Ermöglichen sie auf der einen Seite zwar eine Selbstkontrolle und stellen so potenziell sta- bilisierende Ressourcen für das Individuum dar, schaffen sie auf der anderen Seite auch neue Anforderungen, die es zu erfüllen gilt.
Keywords: self-tracking; Selbsttechnologien; Wearable; Bullet Journal; Personenwaage; Selbstvermessung

Using second-order information in gradient sampling methods for nonsmooth optimization - Gebken, Bennet (arXiv:2210.04579)
In this article, we show how second-order derivative information can be incorporated into gradient sampling methods for nonsmooth optimization. The second-order information we consider is essentially the set of coefficients of all second-order Taylor expansions of the objective in a closed ball around a given point. Based on this concept, we define a model of the objective as the maximum of these Taylor expansions. Iteratively minimizing this model (constrained to the closed ball) results in a simple descent method, for which we prove convergence to minimal points in case the objective is convex. To obtain an implementable method, we construct an approximation scheme for the second-order information based on sampling objective values, gradients and Hessian matrices at finitely many points. Using a set of test problems, we compare the resulting method to five other available solvers. Considering the number of function evaluations, the results suggest that the method we propose is superior to the standard gradient sampling method, and competitive compared to other methods.

Genotype-phenotype mapping with polyominos made from DNA origami tiles - Dreher, Yannik; Fichtler, Julius; Karfusehr, Christoph; Jahnke, Kevin; Xin, Yang; Keller, Adrian; Göpfrich, Kerstin (Biophysical Journal)
Keywords: Biophysics

Enhanced corrosion resistance of epoxy-films on ultra-thin SiOx PECVD film coated laser surface melted Al-alloys - Varghese, J.; Vieth, P.; Xie, X.; Grundmeier, Guido (SN Applied Sciences)
Abstract The influence of ultra-thin SiO x plasma deposited films on the corrosion resistance of adhesive films on a laser surface melted 7075 aluminium alloy was investigated by means of complementary techniques in comparison to the just laser surface melted state. Laser surface melting (LSM) was performed using a continuous wave mode at a wavelength of 1064 nm. Ultra-thin plasma polymer films were deposited from a mixture of hexamethyldisilane (HMDSO), oxygen, and argon by means of an audio-frequency glow discharge. The surface morphology and surface chemistry compositions were investigated by employing field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy (EDX), diffuse reflection infrared Fourier transform spectroscopy, and X-ray photoelectron spectroscopy. The corrosion resistance of plasma polymer coated LSM Al-7075 alloy was studied using linear sweep voltammetry and electrochemical impedance spectroscopy in a chloride-containing electrolyte. The electrochemical studies showed an improved corrosion resistance for plasma film-coated alloys compared to the just laser surface melted state. To study the corresponding surface adhesive properties, the samples were coated with an epoxy amine adhesive. 90°-peel test under humid conditions confirmed the improvement of interfacial wet-adhesion corrosion tests showed a strong improvement of the delamination resistance of adhesives caused by the ultra-thin interfacial SiO x -films.
Keywords: General Earth and Planetary Sciences; General Physics and Astronomy; General Engineering; General Environmental Science; General Materials Science; General Chemical Engineering

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; Arcos, Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos, Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg K.N. (Advanced Materials Interfaces)
Keywords: General Medicine

Combined in-situ attenuated total reflection-Fourier transform infrared spectroscopy and single molecule force studies of poly(acrylic acid) at electrolyte/oxide interfaces at acidic pH - Neßlinger, Vanessa; Orive, Alejandro G.; Meinderink, Dennis; Grundmeier, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos, Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Mentoring-Programm zur Einarbeitung neuer Lehrbeauftragter. Format, Inhalte und Evaluationsergebnisse. - Behrent, Sigrid (Sprachen. Politik. Sprachenpolitik. Der Beitrag der Sprachenzentren zur Hochschule der Zukunft. Dokumentation der 31. Arbeitstagung vom 5.-7. März 2020 an der Europa-Universität Viadrina in Frankfurt (Oder))

Auswirkungen unterschiedlicher Erwärmstrategien auf die quasistatische und zyklische Belastbarkeit von infrarotgeschweißten, glasfaserverstärkten Thermoplastbauteilen - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P. (Joining Plastics)

A Reverse Engineering Approach for Calibrating Frictional Behavior of Contact Models for Numerical Simulation of Solids Conveying in Extruders - Schöppner, Volker; Brüning, Florian; Sommer, L.

Auswirkungen des Vorscherungseinflusses im Extrusionsprozess auf die rheologischen Kennwerte gefüllter Kautschukmischungen - Schöppner, Volker; Kleinschmidt, Dennis; Nillius, U.; Hopmann, C. (GAK)

Auf der Welle zum Mischerfolg - Schöppner, Volker; Dörner, Marius; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Kunststoffe)

BMC-Spritzgießen bricht die Glasfaser - Moritzer, Elmar; Scholle, Maximilian

Influence of process parameter on fiber quality during fiber recycling through thermal fiber recovery - Moritzer, Elmar; Scholle, Maximilian; Tölle, Lisa; Bomm, J. (RFP Rubber Fibres Plastics)

Einfluss der Prozessführung auf die Faserqualität beim Faserrecycling mittels thermischer Faserrückgewinnung - Moritzer, Elmar; Scholle, Maximilian; Tölle, Lisa; Bomm, J. (GAK - Gummi Fasern Kunststoffe)

Estimation and correction of non-isothermal effects of carbon black-filled rubber compounds in viscosity measurements - Schöppner, Volker; Kleinschmidt, Dennis

Filling and Flow Behavior of Novel Wood-Filled Thermoplastic Elastomers - Moritzer, Elmar; Richters, Maximilian

Investigations on the Influence of Viscoelasticity on the Swell Behaviour and Flow Instabilities of Carbon Black-Filled Rubber Compounds - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Limper, A.; Fey, F.; Facklam, M.; Schön, M.

Investigating Different Methods for Numerical Simulation of Temperature Development in a Feed Section of a Single-Screw Extruder - Schöppner, Volker; Brüning, Florian

Integration of IR Based Inline Measurement Systems of the Surface Temperature of Square Hollow Profiles in an Extrusion Process - Schöppner, Volker; Köllermeier, Jonas

Investigation of the Pressure-Throughput Behavior of Different Spiral Shearing Sections on an Analytical and Simulative Basis - Schöppner, Volker; Frank, Maximilian

Modelling of the material degradation of polypropylene on the co-rotating twin-screw extruder - Schöppner, Volker; Altepeter, Matthias; Wanke, S.

Weiterentwicklung eines Verfahrens zur Korrektur von Wandgleiteffekten im Rahmen rheologischer Messungen an gefüllten Kautschukmischungen - Schöppner, Volker; Kleinschmidt, Dennis; Nillius, U.; Hopmann, C. (GAK)

Rückführung zerkleinerter Organobleche - Moritzer, Elmar; Kröker, M.; Scholle, Maximilian

Teilchen-Kunde - Stäube beim mechanischen Recycling faserverstärkter Thermoplaste - Hopp, Matthias; Tölle, Lisa

Vorteilhaftes Prozessverhalten von Wave-Schnecken - Schall, Christoph Wilhelm Theodor

Modeling Business Models: A cross-disciplinary Analysis of Business Model Modeling Languages and Directions for Future Research - Szopinski, Daniel; Massa, Lorenzo; John, Thomas; Kundisch, Dennis; Tucci, Christopher (Communications of the Association for Information Systems)

Non-Lie subgroups in Lie groups over local fields of positive characteristic - Glöckner, Helge (p-Adic Numbers, Ultrametric Analysis, and Applications)
Keywords: 20Exx; 22Exx; 32Cxx

Manifolds of mappings on Cartesian products - Glöckner, Helge; Schmeding, Alexander (Annals of Global Analysis and Geometry)
Keywords: 58D15; 22E65; 26E15; 26E20; 46E40; 46T20; 58A05

Aspects of differential calculus related to infinite-dimensional vector bundles and Poisson vector spaces - Glöckner, Helge (Axioms)
We prove various results in infinite-dimensional differential calculus that relate the differentiability properties of functions and associated operator-valued functions (e.g., differentials). The results are applied in two areas: (1) in the theory of infinite-dimensional vector bundles, to construct new bundles from given ones, such as dual bundles, topological tensor products, infinite direct sums, and completions (under suitable hypotheses); (2) in the theory of locally convex Poisson vector spaces, to prove continuity of the Poisson bracket and continuity of passage from a function to the associated Hamiltonian vector field. Topological properties of topological vector spaces are essential for the studies, which allow the hypocontinuity of bilinear mappings to be exploited. Notably, we encounter kR-spaces and locally convex spaces E such that E×E is a kR-space.

Birkhoff decompositions for loop groups with coefficient algebras - Glöckner, Helge (arXiv:2206.11711)
Starting with a finite-dimensional complex Lie algebra, we extend scalars using suitable commutative topological algebras. We study Birkhoff decompositions for the corresponding loop groups. Some results remain valid for loop groups with valued in complex Banach-Lie groups.

Thermal influence of resistance spot welding on nearby overmoulded plastic metal joints - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Kolbe, Björn; Minch, Steven (IIW2022, Annual Assembly, Commission III)

Characterization of additively manufactured plastic components for direct screwing - Moritzer, Elmar; Held, Christian

Flexible Teilautomatisierung des robotergestützten mechanischen Fügens - Wippermann, Jan; Meschut, Gerson; Stepputat, Marten; Flügge, Wilko (12. Gemeinsames Kolloquium zur Mechanischen Fügetechnik)

Plasmaaktivierung fehlgeschlagen! - Moritzer, Elmar; Rauen, Dennis (Kunststoffe)

Classification characteristics of fine motor experts based on electroencephalographic and force tracking data - Gaidai, Roman; Gölz, Christian Johannes; Mora, K.; Rudisch, J.; Reuter, E.-M.; Godde, B.; Reinsberger, C.; Voelcker-Rehage, C.; Vieluf, S. (Brain Research)
Keywords: Developmental Biology; Neurology (clinical); Molecular Biology; General Neuroscience

Berufsvorbereitende Sprachförderung. Wie werden Schülerinnen und Schüler fit für den Beruf? - Zierau, Cornelia; Jung, Ulla (Fördermagazin: Berufsbezogene Sprachbildung und Sprachförderung Heft 3/2022)

Fördermagazin: Berufsbezogene Sprachbildung und Sprachförderung Heft 3/2022

Inszenierungen von Adoleszenz und Alterität in Wolfgang Herrndorfs Roman „Tschick“ - Zierau, Cornelia (Adoleszenz und Alterität. Synergien aktueller Ansätze der interkulturellen Literaturwissenschaft und Literaturdidaktik. (im Druck))

V-Edge: Virtual Edge Computing as an Enabler for Novel Microservices and Cooperative Computing - Dressler, Falko; Chiasserini, Carla Fabiana; Fitzek, Frank H. P.; Karl, Holger; Lo Cigno, Renato; Capone, Antonio; Casetti, Claudio Ettore; Malandrino, Francesco; Mancuso, Vincenzo; Klingler, Florian; Rizzo, Gianluca A. (IEEE Network)